Visual Culture Analysis in Campaign of Covid-19 - Vivi Varlina; Yasraf Amir Piliang; Ruly Darmawan; Tri Sulistyaningtyas (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2023)
In the contemporary context, the significance of utilizing online media as aninformation portal cannot be overstated. This importance is particularlypronounced during the Covid-19 pandemic, as people actively seek informationthrough online platforms to meet their informational requirements. The primaryobjective of this research is to investigate the visual elements employed in Covid19 campaigns, with each element carrying meaningful representations. Toaccomplish this, the researcher employs visual culture studies to analyze Covid19 campaigns from a neurophysiological perspective. The methodology involvesemploying a semantic differential scale and principal components analysis(PCA) with the participation of 22 respondents, who assess 12 binary pairedadjective concepts. The analysis centers on four images sourced from the onlinemedia platform www.covid19.go.id. The findings indicate that people perceivevisual objects influenced by technology in a manner that involves recognition.Each visual element serves as a representation of knowledge and is linked tospecific ideas. From a modern neurophysiological standpoint, technologymediated visual elements lead to logical and constructive outcomes whileexhibiting unique affordabilities. These research findings impart valuableinsights to the Government of Indonesia, underscoring the importance ofconsidering physiological, affective, and aesthetic aspects of visual elements informulating their pandemic campaign policies.